Corals and Sponges Under the Light of the Holobiont Concept: How Microbiomes Underpin Our Understanding of Marine Ecosystems - Stévenne, Chloé; Micha, Maud; Plumier, Jean-Christophe; Roberty, Stéphane (Frontiers in Marine Science, 2021)
In the past 20 years, a new concept has slowly emerged and expanded to various domains of marine biology research: the holobiont. A holobiont describes the consortium formed by a eukaryotic host and its associated microorganisms including bacteria, archaea, protists, microalgae, fungi, and viruses. From coral reefs to the deep-sea, symbiotic relationships and host–microbiome interactions are omnipresent and central to the health of marine ecosystems. Studying marine organisms under the light of the holobiont is a new paradigm that impacts many aspects of marine sciences. This approach is an innovative way of understanding the complex functioning of marine organisms, their evolution, their ecological roles within their ecosystems, and their adaptation to face environmental changes. This review offers a broad insight into key concepts of holobiont studies and into the current knowledge of marine model holobionts. Firstly, the history of the holobiont concept and the expansion of its use from evolutionary sciences to other fields of marine biology will be discussed. Then, the ecology and physiology of marine holobionts will be investigated through the examples of corals and sponges. We will discuss the impacts of environmental change on organisms at the holobiont level and how microbiomes contribute to the resilience and/or vulnerability of their host in the face of environmental stressors. Finally, we will conclude with the development of new technologies, holistic approaches, and future prospects for conservation biology surrounding marine holobionts.